STRATEGY OF SERICE QUALITY AND PROMOTION OF STUDENT’ TRUST, SATISFACTION AND LOYALTY ( Research on STIE Harapan Bangsa Purwokerto) - Dianningsih, Dianningsih (STIE AUB Surakarta)
The purpose of this research is to know the influence of tangible, reliability, responsiveness, assurance, emphaty, promotion on trust and satisfaction on the loyality of college student in the STIKES Harapan Bangsa Purwokerto. This study is a survey. The data is primary data taken by sampling method, as many as 128 respondents. Data analyzed with validity and reliability test, partial test ( t test ), simultaneously test ( F test ), R-square and path analysis. T test result shows that : physical evidenc is significant positive effect on satisfaction, location is insignific tangibels is significant positive effect on trust, reliability is significant positive effect on trust, responsiveness is significant positive effect on trust, assurance is insignificant negative effect on trust, emphaty is significant positive effect on trust, promotion is significant positive effect on trust, tangible is significant positive effect on satisfaction, reliability is significant positive effect on satisfaction, responsivveness is significant positive effect on satisfaction, assurance is significant positive effect on satisfaction, emphaty is insignificant positive effect on satisfaction,promotion is insignificant negative effect on satisfaction, tangibel is significant positive effect on loyality, reliability is insignificant positive effect on loyality, responsivveness is insignificant positive effect on loyality, assurance is insignificant positive effect on loyality, emphaty is insignificant negative effect on loyality, promotion is significant positive effect on loyality, trust is significant positive effect on loyality, satisfaction is significant positive effect on loyality. F test result shows that simultaneously tangible, reliability, responsiveness, assurance, emphaty, promotion, trust and satisfaction has significant positive effect on the performance. R-square test result shows that 92,9 % variation of loyality can be explained by tangible, reliability, responsiveness, assurance, emphaty, promotion, trust and satisfaction the remaining 7,1% is explained by other factors out of the model. Based on a total leverage to improve loyality will be more effective if through increased promotion. Keywords : tangible, reliability, responsiveness, assurance, emphaty, promotion, trust, satisfaction and loyality